Zeolite washcoating onto cordierite honeycomb reactors for environmental applications - Zamaro, Juan Manuel (2005)
The preparation conditions to obtain zeolite washcoats with optimum loading and homogeneous distribution are studied for mordenite, ferrierite and ZSM5, The slurry concentration and the number of immersions were combined to obtain different coating thickness and geometry. The solid concentration increases the viscosity of the slurry resulting in an exponential growth of the zeolite loading. In order to obtain more homogeneous washcoatings it is preferable to use diluted suspensions and perform more than one immersion. It was found that the washcoating adherence increases with the decrease in the size of the aggregates deposited on the monolith. This improves the packaging and interaction between particles and facilitates a convenient filling of the surface cordierite macropores, producing a more effective anchorage. In this vein, the order of washcoat stability tested with an ultrasound method is ZSM5 > mordenite > ferrierite. The addition of SiO2 as a binder improves the adherence of the three zeolites under study probably due to an improvement in the interparticle cohesion. The performance of an In-ZSM5 washcoated monolith was tested for the selective reduction of NOx with methane under oxygen excess. It was observed that the activity of the monolithic catalyst was as good as those for the In-ZSM5 powder, which indicates that there are no diffusive restrictions due to coating thickness.